Pancasila Education As The Basis For Building and Maintaining The Nation's Character Toward The Era Of Artificial Intelligence - M Rizqon Al Musafiri; Ahmad Irfan Ilhami (Simfoni Ilmu Cindekia, 2026)
The rapid development of Artificial Intelligence (AI) technology has brought significant changes to various aspects of life, including the threat of erosion of the national character of Indonesian society. This community service activity aims to increase public understanding of the importance of Pancasila Education as the ideological foundation in building and maintaining the nation's character in the era of Artificial Intelligence. The activity was held on February 24, 2026 at PP Al Mubarok Genteng, Banyuwangi Regency, involving 80 participants from various community components including santri, community leaders, and the general public of Genteng District. The method used was socialization through presentation of material covering the concepts of Pancasila values, the challenges of the AI era, and strategies for strengthening national character in the digital era. The results showed that participants gave positive responses and high appreciation for the activity, considering it very helpful in understanding the challenges of the AI era based on Pancasila values. It is concluded that Pancasila Education remains highly relevant as a moral compass in facing the challenges of AI development and needs to be continuously socialized to all levels of society.